Analisis Akuntabilitas dan Trasparansi dalam Etika Politik Islam - Nur Ahmad Al Fai’q; Ahmad Faisal; Nur Fadillah; Kurniati Kurniati (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2024)
This research aims to explore the application of the principles of accountability and transparency in Islamic political ethics and its influence on good governance. Accountability is an important element in public sector organizations, as regulated in Government Regulation of the Republic of Indonesia Number 8 of 2006 concerning Financial Reporting and Performance of Government Agencies. Transparency, as another key component, ensures openness in the decision-making process and information delivery. These two principles serve as mechanisms to combat rampant corruption in Indonesia, as reflected in the 2010 Corruption Watch Index score. This study uses a qualitative approach with a literature review method, involving the search and analysis of references from relevant books and journals. This analysis aims to understand how Islamic political ethics integrates the principles of accountability and transparency, as well as the challenges faced in their application. The results of the study show that from an Islamic perspective, accountability is seen as a mandate that must be fulfilled with honesty, justice, and transparency. Transparency in Islam emphasizes the importance of honest and thorough disclosure of information to all interested parties. The application of the principles of accountability and transparency in Islamic political governance has the potential to strengthen moral, social, and religious responsibility, as well as increase public trust in the government. However, challenges such as patronage politics, money politics, and corruption are still major obstacles. To overcome this challenge, there needs to be a strong commitment from the government and the community to implement these principles consistently. Thus, this research makes an important contribution in understanding how the principles of accountability and transparency in Islamic political ethics can be applied to improve good governance and combat corruption in Indonesia.